Public mural art installations in an urban cultural district: place identity under scrutiny - Mat Raschid, Mohammad Yazah; Mohd Tahir, Osman; Karimian, Elham (Universiti Putra Malaysia Press, 2016)
Public Mural Art Installation (PMAI) affects tourist perceptions and decision-making on a destination’s features and the manner they enhance a place identity. Despite the intention, many PMAI seems to have a lack of purpose in conveying its message on the place’s identity to tourists. The construction of the PMAI appeared to be haphazardly implemented and does not integrate well with the open public space to provide appropriate meaning to the place. This paper investigates how tourists’ conceive the manner PMAI in Georgetown Cultural District enhances the identity of the place. A non-participant observation on the tourists behaviors during their engagement with the PMAI and descriptive analysis were conducted in the data collection process. The result demonstrates that both the local and international tourists were attracted to the PMAI and support by the local government through maintenance and events including more accessible and integrated approach in the planning and design of urban open spaces are essentially needed to further sustain the attraction. This study contributes to the creation of more effective construction guidelines concerning the PMAI installation in urban setting.